Theoretical and Methodological Analysis of the Phenomenon of Religious Faith: Socio-Psychological Aspect - Mudrуk A. (Psychological Prospects Journal, 2013)
The results of theoretical-methodological analysis of problem of religious faith are represented in the article. The looks of prominent theologies, philosophers and psychologists are analysed, in relation to the noted question, understanding of the phenomenon of religious faith is presented in modern psychological science and his basic descriptions are described.